Penggunaan Pelarut Acidified Water dalam Perolehan Antosianin dari Kulit Buah Naga Merah menggunakan Microwave Assisted Extraction (MAE) - Shiddiqi, Qifni Yasa Ash; Putri, Tiara Ariani; Hizbiyati, Andini; Prabowo, Bambang Hari; Anwar, Nadiem; Nurramdhania, Anisya; Apriliani, Fatiha (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Dragon fruit peels are agricultural waste products that weigh 30-35% of the fruit. Dragon fruit peels contain anthocyanin natural dyes which are quite high. Anthocyanins are a class of flavonoid compounds which are widely divided into plant polyphenols. Anthocyanins are stable at pH 3.5 and temperature 50. The purpose of this study is to determine the anthocyanin content of dragon fruit peels and also to know the quality of natural dyes produced from anthocyanin dragon fruit peels. Intake of anthocyanin dyes is carried out by the extraction method followed by a distillation process so that the anthocyanin extract becomes more concentrated and can be applied directly as a natural dye. The extraction technique used is Microwave Assisted Extraction (MAE) with acidified water solvent. The acid used is citric acid 10% with a ratio of aquades: citric acid 10% is 3:1 and 8:1 with extraction time of 1,3,5 minutes at 350 watts of power. The content of anthocyanin was analyzed using a UV-VIS spectrophotometer. The best results of the content of anthocyanin were at the extraction time of 5 minutes with a solvent ratio of 3: 1 with a concentration of 36.40 mg /100 g.